2005
DOI: 10.1128/jcm.43.2.813-817.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of the ViroSeq Human Immunodeficiency Virus Type 1 (HIV-1) Genotyping System for Detection of HIV-1 Drug Resistance Mutations by Use of an ABI PRISM 3100 Genetic Analyzer

Abstract: The ViroSeq human immunodeficiency virus type 1 (HIV-1) genotyping system is an integrated system for identification of drug resistance mutations in HIV-1 protease and reverse transcriptase (RT). Reagents are included for sample preparation, reverse transcription, PCR amplification, and sequencing. Software is provided to assemble and edit sequence data and to generate a drug resistance report. We determined the sensitivity and specificity of the ViroSeq system for mutation detection using an ABI PRISM 3100 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…Previous studies have documented high sensitivity and specificity of the ViroSeq system for detection of HIV-1 drug resistance mutations, 1 and excellent performance of ViroSeq for analysis of diverse HIV-1 strains. 10 This report demonstrates that ViroSeq consistently detects the K103N mutation in plasma samples with subtypes A, C, and D at levels over 20% of the viral population, and often detects the K103N mutation at lower levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented high sensitivity and specificity of the ViroSeq system for detection of HIV-1 drug resistance mutations, 1 and excellent performance of ViroSeq for analysis of diverse HIV-1 strains. 10 This report demonstrates that ViroSeq consistently detects the K103N mutation in plasma samples with subtypes A, C, and D at levels over 20% of the viral population, and often detects the K103N mutation at lower levels.…”
Section: Discussionmentioning
confidence: 99%
“…These assays also detect some mutations that are present at lower levels. Using recombinant viral stocks, we previously demonstrated that ViroSeq reliably detects drug resistance mutations present in 40% of the viral population in samples with viral loads from 2000 to 5000 copies/ml 1 , lower level mixtures were not evaluated in that study. In another study, ViroSeq detected the K103N mutation in a recombinant human immunodeficiency virus type 1 (HIV-1) strain at a level of 10%.…”
mentioning
confidence: 99%
“…The FDA-approved ViroSeq assay amplifies an 1.8-kb fragment covering the entire protease region and codons 1 to 335 of the reverse transcriptase (RT) region. This assay has an amplification detection sensitivity of 2,000 RNA copies/ml of plasma and a DR-associated mutation (DRM) detection sensitivity and specificity of 99.65% and 99.95%, respectively (35). Drug resistance genotyping was performed according to the manufacturer's instructions, and DR interpretations were conducted using both the ViroSeq HIV-1 genotyping system software, V2.6, and the Stanford genotyping resistance interpretation algorithm (http://sierra2.stanford.edu/sierra/servlet/JSierra) to allow for comparison with the in-house assay.…”
Section: Methodsmentioning
confidence: 99%
“…The ViroSeq HIV-1 genotyping system was optimized for use on subtype B strains (3) and is currently widely commercialized and used in African settings where non-B HIV-1 strains predominate. The present observations in Cameroon, a country where almost all cocirculating strains are non-B HIV-1 variants, showed the impact of non-B HIV-1 genetic divergence on the performance of this assay.…”
mentioning
confidence: 99%